Opportunities and Challenges of Bali Fatting Business in Napano Kusambi District, Muna Barat Regency - Hermawan Hermawan; Achmad Slamet Aku; Hairil A Hadini (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
This study aims to determine the opportunities and challenges of the Bali cattle fattening business in Napano Kusambi District, West Muna Regency which was carried out in July 2021. Determination of the research location by Purposive Sampling with a sample of 10 respondents/village, with a total of 60 respondents from 6 villages using the method survey utilizing interviews, observation, and documentation and analyzed descriptively. The results of the research on opportunities for developing a Bali cattle fattening business in Napano Kusambi District are the age of the breeder is classified as productive, the experience of raising livestock, the family workforce involved, the ownership of 1-5 cattle, natural grass feed is still available, the ownership of livestock between 1-5 heads, land which is quite extensive and the challenges of developing a fattening business are livestock as a sideline business, the number of males is small, an extensive maintenance system, no addition of concentrate feed, unavailable cages, fattening is still a pasture fattening system, lack of disease management, and lack of livestock extension workers.